2022
DOI: 10.3390/agronomy12081751
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soil Fertility in Tea Gardens Leads to Declines in Fungal Diversity and Complexity in Subsoils

Abstract: Soil fungi are key drivers regulating processes between ecosystem fertility and plant growth; however, the responses of soil fungi community composition and diversity in deeper soil layers to the plantation and fertilization remain limited. Using soil samples along with vertical soil profile gradients with 0–10 cm, 0–20 cm, 20–40 cm, and 40–60 cm in a tea garden, we used Illumina sequencing to investigate the fungal diversity and assemblage complexity, and correlated to the low, middle, and high-level fertiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…With the aggravation of drought stress, Ascomycota shows a significant upward trend, which may be due to the high species diversity and evolution speed of Ascomycota, which is more suitable for the arid environment [34], and Ascomycota is mostly saprophytic bacteria, it plays an essential role in degrading soil organic matter [35]., In this study, Basidiomycota and Glomeromycota decreased with the aggravation of drought stress. Basidiomycota is mostly saprophytic bacteria, which can promote soil material circulation, and many mycorrhizal fungal are Basidiomycota, which are beneficial soil bacteria that can antagonize root pathogens [36], so as to optimize the original soil microbial ecological environment. Glomeromycota is an important arbuscular mycorrhiza in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With the aggravation of drought stress, Ascomycota shows a significant upward trend, which may be due to the high species diversity and evolution speed of Ascomycota, which is more suitable for the arid environment [34], and Ascomycota is mostly saprophytic bacteria, it plays an essential role in degrading soil organic matter [35]., In this study, Basidiomycota and Glomeromycota decreased with the aggravation of drought stress. Basidiomycota is mostly saprophytic bacteria, which can promote soil material circulation, and many mycorrhizal fungal are Basidiomycota, which are beneficial soil bacteria that can antagonize root pathogens [36], so as to optimize the original soil microbial ecological environment. Glomeromycota is an important arbuscular mycorrhiza in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ma et al (2022) in a study conducted on soils of tea plantations revealed that fungal community predominantly consisted Earlier reports indicated that fungal communities in several tea gardens at the genus level are dominated primarily by Saitozyma (Ma et al, 2022;Wang et al, 2023). Members of the Saitozyma, have been shown to account for ~30% of the sequences in tea garden soils in the Southeast Asia region, followed by Mortierella (20%) and Pseudogymnoascus (10%) (Yan P. et al, 2022). Basidiomycota, such as Saitozyma, Russula and Hygrocybe commonly found in tea gardens, are well known to colonize lignin-rich surfaces and likely play significant roles in the degradation of lignin-rich plant litters (Guo et al, 2018;Kui et al, 2021), transforming these substrates to provide carbon and nitrogen as well as other nutrients for plant growth (Li et al, 2020).…”
Section: Fungal Communities In Tea Gardens Soilsmentioning
confidence: 95%